Precursor for forming scandium-containing or yttrium-containing thin film, method for forming scandium-containing or yttrium-containing thin film using said precursor, and semiconductor element comprising said scandium-containing or yttrium-containing thin film
By developing a new precursor for the formation of scandium or yttrium films containing amidino ligands, the problems of high viscosity and low vapor pressure during the film formation process in the prior art have been solved, and the formation of high-quality films and the improvement of leakage current performance have been achieved.
Patent Information
- Application Number
- CN202380048828.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-30
- Filing Date
- 2023-11-30
- Publication Date
- 2025-02-28
AI Technical Summary
When forming high dielectric films, the leakage current caused by the band gap is greatly degraded, and the actinium metal precursors used in film formation projects have problems such as high viscosity and low vapor pressure, which limits the performance improvement of semiconductor components.
A new scandium or yttrium film formation precursor containing amidino ligand has a low viscosity, high heat resistance and high volatility. By improving the chemical structure of the precursor, a high-quality scandium or yttrium film is formed.
The structural stability and performance improvement of the precursor compounds used in film formation engineering has been achieved. The formed film has low viscosity, high heat resistance and high volatility. It is suitable for the manufacturing of high dielectric films, significantly improving leakage current performance.
Smart Images

Figure CN119546799A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a precursor for forming a scandium (Sc) or yttrium (Y) thin film, a method for forming a scandium or yttrium thin film using the precursor, and a semiconductor component containing the scandium or yttrium thin film, and more particularly to a precursor for forming a scandium or yttrium thin film that can form a low viscosity, high heat resistance, and high volatility precursor through a chemical structure containing an amidine ligand, thereby forming a high-quality thin film, a method for forming a thin film using the precursor, and a semiconductor component containing the thin film. Background Art
[0002] As the integration level of semiconductor components is improved due to the miniaturization of the line width, the space allowed for realizing the capacitor structure is limited by the line width. Therefore, the manufacturing method of semiconductor components for realizing the capacitor structure is also limited in the existing silicone dielectrics. In particular, when high dielectric films are used to replace silicone dielectrics, the leakage current will be greatly degraded due to the band gap. As one of the solutions to the above problems, a technology that can form high-quality films is needed, and for this purpose, the precursors used in forming the films need to be optimized.
[0003] To this end, a variety of actinium metal precursors have been developed. For example, Korean Patent Publication No. 10-2019-0008427 discloses an actinium metal precursor containing an azallyl ligand, and Korean Patent Publication No. 10-2019-0094238 discloses an actinium metal precursor containing a cyclopentadienyl ligand.
[0004] In particular, the cyclopentadienyl-containing complex has a lower melting point and higher volatility than the β-diketone- or bis(trimethylsilyl)amide-containing compounds, and is therefore more advantageously used as a precursor in the thin film forming process.
[0005] For the reasons mentioned above, in the known technologies such as Korean registered patent No. 10-1660052, Korean published patent No. 10-2019-0109142 and No. 10-2021-0084297, a chemical structure combining a cyclopentadienyl group and an amidine group as a ligand as an actinium metal precursor is proposed. The report points out that the precursor combined with the ligand as described above can improve the disadvantages of the existing actinium metal precursor with low vapor pressure and high viscosity, and is suitable for use in thin film formation engineering.
[0006] It has been confirmed from the prior art as described above that it is expected that the chemical properties of the precursor can be improved by applying an amidine ligand to a metal-containing precursor compound. Summary of the invention
[0007] An object of the present invention is to solve the problems existing in the prior art as described above and to provide a novel scandium or yttrium-containing thin film forming precursor that can exhibit chemical properties suitable for a thin film forming precursor.
[0008] Another object of the present invention is to provide a scandium or yttrium-containing thin film-forming precursor exhibiting chemical characteristics of low viscosity, high heat resistance, and high volatility.
[0009] Another object of the present invention is to provide a method for forming a thin film using the precursor.
[0010] Another object of the present invention is to provide a semiconductor component comprising the thin film.
[0011] In order to achieve the above-mentioned object, the scandium- or yttrium-containing thin film forming precursor of the present invention is characterized by comprising a compound represented by the following Chemical Formula 1.
[0012]
Chemical formula 1
[0013]
[0014] In the chemical formula 1, M is scandium (Sc) or yttrium (Y), R1 and R3 are each independently a C1-C5 linear, branched or cyclic alkyl or alkenyl group, and R2 is a hydrogen atom or a C1-C6 linear, branched or cyclic alkyl or alkenyl group.
[0015] In addition, in the chemical formula 1, the R2 may be a C2-C4 linear, branched or cyclic alkyl or alkenyl group.
[0016] In addition, the R1 and R3 may each independently be a C2-C5 straight chain, branched chain or cyclic alkyl or alkenyl group, and the R2 may be a C2-C4 straight chain, branched chain or cyclic alkyl or alkenyl group.
[0017] In addition, the R1 and R3 may be methyl groups, and the R2 may be isopropyl groups.
[0018] In addition, the R1 and R3 may be C1-C5 straight-chain alkyl or alkenyl groups.
[0019] In addition, the R1 and R3 may be a C1-C5 straight-chain alkyl or alkenyl group, and the R2 may be a C1-C4 straight-chain alkyl or alkenyl group.
[0020] Furthermore, the R1 and R3 may all be the same, and may be an alkyl group or an alkenyl group.
[0021] Furthermore, the R1 to R3 may all be the same, and may be an alkyl group or an alkenyl group.
[0022] Furthermore, the thin film forming precursor may have a structure as described below.
[0023] Furthermore, the thin film forming precursor may have a viscosity of 60 cP or less and a melting point of 70° C. or less.
[0024] In addition, the thin film forming precursor may further contain a solvent, and the solvent may be C1-C 16 The thin film forming precursor may contain 1 to 99 wt % of the solvent relative to the total weight of the thin film forming precursor.
[0025] The method for forming a scandium or yttrium-containing thin film of the present invention is characterized in that it includes a process of forming a thin film on a substrate using the thin film forming precursor, and the process of forming a thin film on a substrate includes a process of forming a precursor thin film by depositing the thin film forming precursor on the surface of the substrate and a process of reacting the precursor thin film with a reactant.
[0026] Furthermore, the step of forming a precursor thin film may include a step of vaporizing the thin film forming precursor and transferring the vaporized thin film forming precursor into a chamber.
[0027] In addition, the deposition can be performed by one of the following projects: spin-on dielectric (SOD) project, low temperature plasma (LTP) project, chemical vapor deposition (CVD) project, plasma chemical vapor deposition (PECVD) project, high density plasma chemical vapor deposition (HDPCVD) project, atomic layer deposition (ALD) project or plasma atomic layer deposition (PEALD) project.
[0028] In addition, the process of forming a thin film on the substrate may be performed at a temperature ranging from 150 to 500°C.
[0029] In addition, the reactant can be one or more of nitrogen (N2), ammonia (NH3), hydrazine (N2H4), nitrous oxide (N2O), oxygen (O2), water vapor (H2O), ozone (O3), hydrogen peroxide (H2O2), silane, hydrogen (H) and diborane (B2H6).
[0030] Furthermore, the process of forming a thin film containing scandium or yttrium on a substrate may include a step of forming the thin film by supplying the thin film forming precursor to the substrate and applying plasma.
[0031] Furthermore, the scandium- or yttrium-containing thin film of the present invention is characterized in that it can be formed using the thin film forming precursor, and the semiconductor device of the present invention includes the thin film produced by the scandium- or yttrium-containing thin film forming method.
[0032] According to the scandium or yttrium-containing thin film forming precursor of the present invention, the excellent structural stability of the precursor compound is ensured by containing an amidine ligand and exhibits the characteristics of low viscosity, high volatility and high heat resistance, thereby exhibiting physical properties suitable for use in the scandium or yttrium-containing thin film forming process.
[0033] Furthermore, a scandium or yttrium-containing thin film can be formed using the precursor, and a semiconductor component including the scandium or yttrium-containing thin film produced by the thin film formation method can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the result of hydrogen nuclear magnetic resonance (1H NMR) analysis of tris(diethyl-n-propylamidino)yttrium.
[0035] Figure 2 This is the result of thermogravimetric analysis (TGA) of tris(diethyl-n-propylamidino)yttrium.
[0036] Figure 3 It is the differential scanning calorimetry (DSC) analysis result of tris(diethyl-n-propylamidino)yttrium.
[0037] Figure 4 This is the result of 1H NMR analysis of tri(diethyl-ethylamidino)yttrium.
[0038] Figure 5 It is the result of thermogravimetric analysis (TGA) of tris(diethyl-ethylamidino)yttrium.
[0039] Figure 6 This is the result of hydrogen nuclear magnetic resonance (1H NMR) analysis of tri(di-n-propyl-ethylamidino)yttrium.
[0040] Figure 7It is the result of thermogravimetric analysis (TGA) of tri(di-n-propyl-ethylamidino)yttrium.
[0041] Figure 8 This is the result of 1H NMR analysis of tri(diethyl-n-butylamidino)yttrium.
[0042] Fig. 9 This is the result of thermogravimetric analysis (TGA) of tri(diethyl-n-butylamidino)yttrium.
[0043] Fig.10 This is the result of hydrogen nuclear magnetic resonance (1H NMR) analysis of tris(diethyl-n-propylamidino)scandium.
[0044] Fig.11 This is the result of thermogravimetric analysis (TGA) of tris(diethyl-n-propylamidino)scandium.
[0045] Fig.12 It is the result of differential scanning calorimetry (DSC) analysis of tris(diethyl-n-propylamidino)scandium.
[0046] Fig.13 This is the result of hydrogen nuclear magnetic resonance (1H NMR) analysis of tris(diethyl-ethylamidino)scandium.
[0047] Fig.14 This is the result of thermogravimetric analysis (TGA) of tris(diethyl-ethylamidino)scandium.
[0048] Fig.15 This is a graph showing the change in film thickness (film deposition rate) according to different deposition cycle numbers in a thin film formation process using tris(diethyl-n-propylamidino)yttrium as a precursor under process conditions of 300°C.
[0049] Fig.16 This is a graph showing the change in film deposition rate (ALD window) at different temperatures in a thin film formation process using tris(diethyl-n-propylamidino)yttrium as a precursor.
[0050] Fig.17 The X-ray diffraction (XRD) analysis results of thin films deposited at 300° C. using tris(diethyl-n-propylamidino)yttrium as a precursor.
[0051] Fig.18 The results of X-ray electron spectroscopy (XPS) analysis of thin films deposited at 300° C. using tris(diethyl-n-propylamidino)yttrium as a precursor.
[0052] Fig.19The dielectric constant and current density of thin films deposited at 300°C using tris(diethyl-n-propylamidino)yttrium as a precursor are measured. DETAILED DESCRIPTION
[0053] Next, the present invention will be described in more detail. The terms or words used in this specification and claims should not be interpreted in a general or dictionary sense, but should be interpreted based on the principle that the inventor can appropriately define the concept of the term in order to describe his invention in the best way, so as to conform to the meaning and concept of the technical idea of the present invention.
[0054] The scandium- or yttrium-containing thin film forming precursor according to the present invention is characterized by including a compound represented by the following Chemical Formula 1.
[0055]
Chemical formula 1
[0056]
[0057] In the chemical formula 1, M is scandium or yttrium metal, R1 and R3 are each independently a C1-C5 linear, branched or cyclic alkyl or alkenyl group, and R2 is a hydrogen atom or a C1-C6 linear, branched or cyclic alkyl or alkenyl group.
[0058] In the amidine ligand, R1 and R3 may be the same or different, and the ligand in which R1 and R3 contain the same symmetrical structure exhibits better effects in terms of heat resistance and viscosity.
[0059] In addition, in the chemical formula 1, R2 constituting the amidine ligand may be a hydrogen atom or a C1-C4 straight chain, branched chain or cyclic alkyl or alkenyl group, preferably including a normal alkyl group such as ethyl, propyl and butyl.
[0060] The thin film forming precursor may be formed into compounds of various forms depending on the type of functional groups.
[0061] In one embodiment, the R2 in the chemical formula 1 may be a C2-C4 linear, branched or cyclic alkyl or alkenyl group.
[0062] In addition, the R1 and R3 may each independently be a C2-C5 straight chain, branched chain or cyclic alkyl or alkenyl group, and the R2 may be a C2-C4 straight chain, branched chain or cyclic alkyl or alkenyl group.
[0063] In addition, the R1 and R3 may be methyl groups, and the R2 may be isopropyl groups.
[0064] In addition, the R1 and R3 may be C1-C5 straight-chain alkyl or alkenyl groups.
[0065] In addition, the R1 and R3 may be a C1-C5 straight-chain alkyl or alkenyl group, and the R2 may be a C1-C4 straight-chain alkyl or alkenyl group.
[0066] Furthermore, the R1 and R3 may all be the same, and may be an alkyl group or an alkenyl group.
[0067] Furthermore, the R1 and R3 may all be the same, and may be an alkyl group or an alkenyl group.
[0068] Furthermore, the thin film forming precursor may have a structure as described below.
[0069] As the thin film forming precursor described above, the following chemical structures can be exemplified.
[0070]
[0071]
[0072] The compound represented by the chemical formula 1 is a precursor having scandium or yttrium as the central metal atom and containing an amidine ligand, has low viscosity and high thermal stability and volatility and can be in liquid form at room temperature. Therefore, by synthesizing a precursor containing the ligand, the desired chemical properties of the precursor can be obtained.
[0073] Specifically, the thin film forming precursor may have a viscosity of 60 cP or less and a melting point of 70° C. or less.
[0074] By adopting the chemical structure of the thin film forming precursor as described above, a liquid precursor having low viscosity, high heat resistance and high volatility can be obtained, thereby forming a high-quality thin film.
[0075] In addition, considering the conditions and efficiency of the thin film forming process, the thin film forming precursor of the present invention may further contain a solvent for dissolving or diluting the precursor compound. As the solvent, C1-C 16 One or a mixture of saturated or unsaturated hydrocarbons, ketones, ethers, glycol dimethyl ether, esters, tetrahydrofuran and tertiary amines. 16 Examples of saturated or unsaturated hydrocarbons include toluene and heptane, and examples of tertiary amines include dimethylethylamine.
[0076] In particular, the compound of the thin film forming precursor may be in a solid state at room temperature according to its chemical structure, and in the case as described above, the compound can be dissolved by including the solvent. That is, when the solvent is included, the solvent that can dissolve the precursor compound and the content thereof are preferably 1 to 99% by weight relative to the total weight of the thin film forming precursor.
[0077] Since the precursor containing or not containing the solvent can be gasified, it can be supplied into the chamber in the form of precursor gas. Therefore, depending on the type of the precursor compound for thin film formation, when it exists in a liquid state at room temperature and can be easily gasified, a thin film formation process can be performed without using a separate solvent.
[0078] In addition, the scandium or yttrium-containing thin film formation process can be performed by one of the following projects: dielectric spin coating (spin-ondielectric, SOD) project, low temperature plasma (Low Temperature Plasma, LTP) project, chemical vapor deposition (Chemical Vapor Deposition, CVD) project, plasma chemical vapor deposition (Plasma Enhanced Chemical Vapor Deposition, PECVD) project, high density plasma chemical vapor deposition (High Density Plasma-Chemical Vapor Deposition, HDPCVD) project, atomic layer deposition (Atomic Layer Deposition, ALD) project or plasma atomic layer deposition (Plasma Enhanced Atomic Layer Deposition, PEALD) project.
[0079] For example, when the high-density plasma chemical vapor deposition (HDP-CVD) process is applied, it can be performed under high vacuum and high power compared to the atmospheric pressure chemical vapor deposition process (AP-CVD), low pressure chemical vapor deposition process (LP-CVD) or plasma enhanced chemical vapor deposition process (PE-CVD), so a thin film with a dense structure and excellent mechanical properties can be formed.
[0080] To this end, the thin film forming method according to the present invention includes a step of forming a thin film on a substrate using the thin film forming precursor.
[0081] Specifically, the process of forming a scandium or yttrium-containing thin film on the substrate may include a process of forming a precursor thin film by depositing the thin film forming precursor on the surface of the substrate and a process of reacting the precursor thin film with a reactant.
[0082] Furthermore, the method may include a step of vaporizing the thin film forming precursor and transferring the vaporized thin film forming precursor into a chamber for deposition of the precursor.
[0083] In addition, the process of forming a scandium or yttrium-containing thin film on the substrate may include a process of forming a thin film of metal, oxide, nitride, oxynitride, etc. by supplying the thin film forming precursor to the substrate and applying plasma in the presence of a reactant.
[0084] The film forming process can be performed under a chamber pressure condition of 1 to 1000 mTorr. In addition, the source power for forming plasma in the chamber is preferably 500 to 9,000 W, and the bias power is preferably 0 to 5,000 W. In addition, the bias power may not be applied according to specific circumstances.
[0085] In addition, the process of forming a thin film on the substrate may be performed at a temperature ranging from 150 to 500°C.
[0086] In addition, when supplying the thin film forming precursor, in order to further improve the electrical properties of the metal film finally formed, i.e., the electrostatic capacitance or the leakage current value, a second metal precursor can be introduced as needed. The second metal precursor can also selectively further supply a metal precursor containing one or more metals (M") selected from silicon (Si), titanium (Ti), germanium (Ge), strontium (Sr), niobium (Nb), barium (Ba), hafnium (Hf), tantalum (Ta) and actinium (Ac) atoms. The second metal precursor can be an alkylamide compound or an alkoxy compound containing the metal. As an example, when the metal is Si, as the second metal precursor, SiH(N(CH3)2)3, Si(N(C2H5)2)4, Si(N(C2H5)(CH3))4, Si(N(CH3)2)4, Si(OC4H9)4, Si(OC2H5)4, Si(OCH3)4 and Si(OC(CH3)3)4 can be used.
[0087] The supply of the second metal precursor may be performed in the same manner as the supply method of the thin film forming precursor, the second metal precursor may be supplied together with the precursor onto the thin film forming substrate, or may be supplied sequentially after the supply of the precursor is completed.
[0088] In order to contact the thin film forming substrate, the thin film forming precursor and the optional second metal precursor as described above are preferably maintained at a temperature of 50 to 250° C., preferably 100 to 200° C. before being supplied into the reaction chamber.
[0089] In addition, after the precursor supply step and before the reactant is supplied, an engineering of purging an inert gas such as argon (Ar), nitrogen (N2) or helium (He) into the reactor can be performed to help the precursor and the optional second metal precursor move above the substrate, or to form a pressure suitable for deposition in the reactor, and to discharge impurities and the like present in the chamber to the outside. At this time, it is preferable to make the pressure in the reactor reach 1 to 5 Torr by purging the inert gas.
[0090] In addition, as the reactant, one or more of nitrogen (N2), ammonia (NH3), hydrazine (N2H4), nitrous oxide (N2O), oxygen (O2), water vapor (H2O), ozone (O3), hydrogen peroxide (H2O2), silane, hydrogen (H) and diborane (B2H6) can be used. When the process is carried out in the presence of oxidizing gases such as water vapor, oxygen and ozone, a magnesium oxide film can be formed, and when the process is carried out in the presence of reducing gases such as hydrogen, ammonia, hydrazine and silane, a metal monomer or metal nitride film can be formed. In addition, a metal oxynitride film can be formed by mixing the reactants.
[0091] In addition to the plasma treatment, a heat treatment or light irradiation treatment process may be performed to provide thermal energy for depositing a thin film forming precursor, and the treatment process may be performed according to a general method. Preferably, in order to produce a thin film having a desired physical state and composition at a sufficient growth rate, the treatment process is performed at a substrate temperature of 100 to 1,000° C., preferably 250 to 400° C. in the reactor.
[0092] In addition, during the processing process, the process of purging an inert gas such as argon (Ar), nitrogen (N2) or helium (He) into the interior of the reactor as described above can also be performed to help the reactants move to the top of the substrate, or to form a pressure suitable for deposition in the reactor, and to discharge impurities or by-products present in the reactor to the outside.
[0093] The thin film can be formed by taking the above-mentioned steps of charging the thin film forming precursor, charging the reactant, and charging the inert gas as one cycle and repeating the cycle one or more times.
[0094] Furthermore, by applying the thin film forming process, various semiconductor devices including thin films can be manufactured.
[0095] Synthesis Example 1: Synthesis of tris(diethyl-n-propylamidino)yttrium [Y(Et2nPr-AMD)3]
[0096] After adding 65.57 g (0.4609 mol) of di-n-propyl-ethyl amidine to 300 ml of tetrahydrofuran (THF) and cooling to -78°C, 184.4 ml (0.4609 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added dropwise to produce Li-(Et2nPr-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2nPrAMD) solution was slowly added dropwise to a flask containing 30 g (0.4609 mol) of YCl3 at -78°C and stirred at room temperature for 6 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 200 ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. The yellow liquid was distilled at 156°C and 30.1 mTorr to obtain a light yellow liquid. The yield was 61.10 g (77.6%). The NMR (Bruker AV400 MHz HD) analysis results are as follows: Figure 1 as shown, and its characteristic peak is shown below.
[0097] 1 H NMR (C6D6, 25℃): 0.087(t,3H), 1.32(t,6H), 1.52(q,2H), 2.21(q,2H), 3.24(q,4H).
[0098] The results of the analysis of the pale yellow liquid by thermogravimetric analysis (TGA, TA instrument company SDTQ600) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min were 0.1%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Figure 2 shown.
[0099] After the pale yellow liquid sample was placed in a sealed container for differential scanning calorimetry (DSC, Discovery 25 of TA Instrument Co., Ltd.) and maintained at 40°C for 10 minutes, a decomposition peak was observed at 410°C during the DSC analysis at a temperature increase rate of 10°C / min. The results are shown as DSC analysis results showing the change in thermal energy according to the temperature change. Figure 3 shown.
[0100] Synthesis Example 2: Synthesis of tris(diethyl-ethylamidino)yttrium [Y(Et2Et-AMD)3]
[0101] After adding 59.10 g (0.4609 mol) of diethyl-ethyl amidine ester to 300 ml of tetrahydrofuran (THF) and cooling to -78°C, 184.4 ml (0.4609 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added dropwise to produce Li-(Et2Et-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2Et-AMD) solution was slowly added dropwise to a flask containing 30 g (0.4609 mol) of YCl3 at -78°C and stirred at room temperature for 6 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 200 ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. The yellow liquid was distilled at 160°C and 30 mTorr to obtain a light yellow solid. The yield was 52.4 g (72.5%). The NMR (Bruker AV400 MHz HD) analysis results are as follows: Figure 4 as shown, and its characteristic peak is shown below.
[0102] 1 H NMR (C6D6, 25°C): 0.98 (t, 3H), 1.29 (t, 6H), 2.14 (q, 2H), 3.20 (q, 4H).
[0103] The result of the analysis of the pale yellow solid by thermogravimetric analysis (TGA, TA instrument company SDT Q600) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min was 1.4%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Figure 5 shown.
[0104] Synthesis Example 3: Synthesis of tri(di-n-propyl-ethylamidino)yttrium [Y(nPr2Et-AMD)3]
[0105] After adding 71.01 g (0.4609 mol) of di-n-propyl-ethyl amidine to 300 ml of tetrahydrofuran (THF) and cooling to -78°C, 184.4 ml (0.4609 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added dropwise to produce Li-(nPr2Et-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(nPr2EtAMD) solution was slowly added dropwise to a flask containing 30 g (0.4609 mol) of YCl3 at -78°C and stirred at room temperature for 6 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 200 ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. The yellow liquid was distilled at 221°C and 42.6 mTorr to obtain a light yellow solid. The yield was 55.30 g (64.9%). The NMR (Bruker AV400 MHz HD) analysis results are as follows: Figure 6 as shown, and its characteristic peak is shown below.
[0106] 1 H NMR (C6D6, 25°C): 1.02 (t, 9H), 1.71 (q, 4H), 2.22 (q, 2H), 3.18 (q, 4H).
[0107] The result of the analysis of the pale yellow solid by thermogravimetric analysis (TGA, TA instrument company SDT Q600) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min was 0.75%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Figure 7 shown.
[0108] Synthesis Example 4: Synthesis of tri(diethyl-n-butylamidino)yttrium [Y(Et2nBu-AMD)3]
[0109] 120.05 g (0.7682 mol) of diethyl-n-butyl amidinate was added to 300 ml of tetrahydrofuran (THF) and cooled to -78°C, followed by slowly dropping 307.3 ml (0.7682 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) to produce Li-(Et2nBu-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2nBu-AMD) solution was slowly dropped into a flask containing 30 g (0.2561 mol) of YCl3 at -78°C and stirred at room temperature for 6 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 200 ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. The generated orange-yellow liquid was distilled at 210°C and 141 mTorr to obtain a light yellow liquid. The yield was 116.0 g (81.7%). The NMR (Bruker AV400 MHz HD) analysis results are as follows: Figure 8 as shown, and its characteristic peak is shown below.
[0110] 1 H NMR(C6D6,25℃):0.850(t,3H),1.28(q,2H),1.35(t,6H),1.50(m,2H),2.25(m,2H),3.29(q,4H).
[0111] The result of the analysis of the pale yellow solid by thermogravimetric analysis (TGA, TA instrument company SDT Q600) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min was 1.67%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Fig. 9 shown.
[0112] Synthesis Example 5: Synthesis of tris(diethyl-n-propylamidino)scandium [Sc(Et2nPr-AMD)3]
[0113] After adding 58.79 g (0.3965 mol) of di-n-propyl-ethyl amidine to 300 ml of tetrahydrofuran (THF) and cooling to -78°C, 158.61 ml (0.3965 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added dropwise to produce Li-(Et2nPr-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2nPrAMD) solution was slowly added dropwise to a flask containing 20 g (0.3965 mol) of ScCl3 at -78°C and stirred at room temperature for 6 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 150 ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. The yellow liquid was distilled at 185°C and 18.0 mTorr to obtain a light yellow liquid. The yield was 56.80 g (78.6%). The NMR (Bruker AV400 MHz HD) analysis results are as follows: Fig.10 as shown, and its characteristic peak is shown below.
[0114] 1 H NMR (C6D6, 25℃): 0.088(t,3H), 1.30(t,6H), 1.51(q,2H), 2.18(q,2H), 3.26(q,4H).
[0115] The result of the analysis of the pale yellow liquid by thermogravimetric analysis (TGA, TA instrument company SDT Q600) at a nitrogen flow rate of 200 ml / min and a heating rate of 10°C / min was 0.19%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Fig.11 shown.
[0116] The pale yellow liquid sample was placed in a sealed container for differential scanning calorimetry (DSC, Discovery 25 of TA Instrument Co., Ltd.) and maintained at 40°C for 10 minutes. During the DSC analysis period, the temperature was increased at a rate of 10°C / min, and a decomposition peak was observed at 450°C. The results are shown as DSC analysis results that show the change in thermal energy according to the temperature change. Fig.12 shown.
[0117] Synthesis Example 6: Synthesis of tris(diethyl-ethylamidino)scandium [Sc(Et2Et-AMD)3]
[0118] After adding 50.84 g (0.3965 mol) of diethyl-ethyl amidine ester to 300 ml of tetrahydrofuran (THF) and cooling to -78°C, 158.6 ml (0.3965 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added dropwise to produce Li-(Et2Et-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2Et-AMD) solution was slowly added dropwise to a flask containing 20 g (0.3965 mol) of ScCl3 at -78°C and stirred at room temperature for 6 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 150 ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. The yellow liquid was distilled at 145°C and 28.3 mTorr to obtain a light yellow solid. The yield was 41.8 g (74.1%). The NMR (Bruker AV400 MHz HD) analysis results are as follows: Fig.13 as shown, and its characteristic peak is shown below.
[0119] 1 H NMR (C6D6, 25°C): 0.99 (t, 3H), 1.28 (t, 6H), 2.15 (q, 2H), 3.20 (q, 4H).
[0120] The result of the analysis of the pale yellow solid by thermogravimetric analysis (TGA, TA instrument company SDT Q600) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min was 0.3%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Fig.14 shown.
[0121] Thermogravimetric analysis (TGA) analysis results measured on the precursors according to Synthesis Examples 1 to 6 are shown in Table 1.
[0122]
Table 1
[0123]
[0124] Table 2 shows the results of thermogravimetric analysis (DSC) of the precursors obtained in Synthesis Example 1, Synthesis Example 3, and Synthesis Example 5.
[0125]
Table 2
[0126] Synthesis example 1 Synthesis example 3 Synthesis example 5 DSC(℃) 410 399 453
[0127] In order to confirm the viscosity of the precursors of Synthesis Examples 1 and 5, the samples were placed in the measuring container of a rotational viscometer (LVD2T manufactured by Brookfield) and the viscosity was measured at 25°C using a low viscosity rotor. The results are shown in Table 3.
[0128]
Table 3
[0129] Synthesis example 1 Synthesis example 5 Viscosity(cPs) 48 36
[0130] A thin film forming process was carried out using the precursor as described below.
[0131] The film formation evaluation by the atomic layer deposition process was carried out by bubbling method using the precursor of Synthesis Example 1 and O3 as an oxidant. The film formation evaluation used the change in film thickness according to the number of process cycles (Number of cycles vs. Thickness) as an indicator.
[0132] After the precursor of Synthesis Example 1 is heated to a vaporization temperature, argon (Ar) gas is injected through a dip line to generate bubbles, thereby supplying vapor of the precursor compound of the gas phase into the reaction chamber by means of a carrier gas.
[0133] A SiO2 substrate and a TiN substrate were placed in the reaction chamber and a deposition evaluation was performed under the conditions of precursor (60 seconds)-purge (80 seconds)-oxidant (15 seconds)-purge (20 seconds) in order to confirm the change in film thickness according to the number of process cycles while maintaining the set temperature (300°C).
[0134] The purge process was performed using argon (Ar) gas at a flow rate of 700 sccm, and ozone (O3) as a reaction gas at a flow rate of 220 g / m 3 The precursor was heated to 80°C, and the injection rate of argon carrier gas was 200 sccm. The number of processes was 50, 100, and 150. The film thickness change results according to the number of deposition cycles in the 300°C process are shown in the figure. Fig.15 shown.
[0135] See also Fig.15 As a result, for both the evaluated SiO2 and TiN specimens, a certain film thickness variation according to the number of deposition cycles can be observed under engineering temperature conditions.
[0136] In addition, the deposition rates of different substrates at 300 °C are shown in Table 4.
[0137]
Table 4
[0138] @300℃ <![CDATA[SiO2 substrate]]> TiN substrate Deposition rate (nm / cycle) 0.099 0.083
[0139] In addition, in order to confirm the change in deposition rate (ALD window) at a process temperature of 300°C, after the precursor according to the synthesis example 3 was heated to the vaporization temperature, argon (Ar) gas was injected through the production line (DIP line) to generate bubbles, thereby supplying the vapor of the precursor compound of the gas yellow stage into the interior of the reaction chamber with the help of a transport gas.
[0140] SiO2 and TiN substrates were placed in the reaction chamber and supplied in the order of precursor (60 seconds)-purge (80 seconds)-oxidant (15 seconds)-purge (20 seconds) to confirm the change in film deposition rate according to process temperature while changing the temperature. Argon (Ar) gas was supplied at a flow rate of 70 sccm as purge gas. As reaction gas, argon (Ar) gas was supplied at a flow rate of 220 g / m 3 Ozone (O3) was injected at a concentration of 1.5 %. The precursor was heated to 80°C, and the injection rate of argon carrier gas was 200 sccm. The number of processes was 50. The film deposition rate changes according to the process temperature are shown in the following figure. Fig.16 shown.
[0141] See also Fig.16 The results show that similar film deposition rates (nm / cycle) are presented at process temperatures of 275°C and 300°C, thereby confirming that it has a process temperature range (ALD window).
[0142] In addition, in order to confirm the crystallinity of the thin film at different process temperatures, X-ray diffraction (XRD) analysis was performed on the Y2O3 thin films obtained at different temperatures in the SiO2 and TiN test pieces through the process evaluation, thereby confirming the crystallinity of the thin film. The crystallinity was measured after the deposition process, and the test pieces were also analyzed after heat treatment using rapid thermal annealing (RTA) at 600°C, 30 seconds and N2 conditions. The analysis results confirmed that for the thin film just after deposition, cubic Y2O3 crystallinity was observed in the thin film deposited at 300°C, while more cubic Y2O3 crystallinity was observed after the heat treatment. The analyzed X-ray diffraction (XRD) results are as follows Fig.17 shown.
[0143] In addition, X-ray electron spectroscopy depth analysis (XPS depth profile) was performed to confirm the composition and impurities of the film. For the Y2O3 film deposited at 300°C in SiO2 and TiN test pieces, the film composition and impurity content were confirmed by X-ray electron spectroscopy (XPS) analysis. It was observed that the C and N impurities in the film were both 0%, while the O / Y content ratio was O / Y=1.19 on the SiO2 substrate and O / Y=1.26 on the TIN substrate. The results of the analyzed X-ray electron spectroscopy depth analysis (XPS depth profile) are as follows: Fig.18 shown.
[0144] In addition, in order to confirm the electrical properties of the film, TiN was deposited on the top of the deposited film as the upper electrode and its dielectric constant and current density were measured. The results are shown in Table 5 and Fig.19 shown.
[0145]
Table 5
[0146]
[0147] From the above results, it was confirmed that a high-quality scandium or yttrium-containing thin film can be formed using the thin film-forming precursor of the present invention.
[0148] The present invention has been described with reference to preferred embodiments in the above content, but the present invention is not limited to the embodiments, and a person having general knowledge in the technical field to which the present invention belongs can make various modifications and changes to the present invention without departing from the gist of the present invention. These modifications and changes should be understood to be included in the scope of the claims attached to the present invention.
Claims
1. A precursor for forming a scandium or yttrium thin film, characterized in that: Contains a scandium or yttrium-containing compound represented by the following chemical formula 1: 【Chemical formula 1】 In the chemical formula 1, M is scandium or yttrium metal, R1 and R3 are each independently a C1-C5 straight chain, branched chain or cyclic alkyl or alkenyl group, and R2 is a hydrogen atom or a C1-C6 straight chain, branched chain or cyclic alkyl or alkenyl group.
2. The scandium or yttrium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, R2 is a C2-C4 linear, branched or cyclic alkyl or alkenyl group.
3. The scandium or yttrium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, R1 and R3 are each independently a C2-C5 straight chain, branched chain or cyclic alkyl or alkenyl group, and R2 is a C2-C4 straight chain, branched chain or cyclic alkyl or alkenyl group.
4. The scandium or yttrium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, R1 and R3 are methyl groups.
5. The scandium or yttrium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, the R2 is an isopropyl group.
6. The scandium or yttrium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, R1 and R3 are each independently a C1-C5 straight-chain alkyl or alkenyl group.
7. The scandium or yttrium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, R1 and R3 are each independently a C1-C5 straight-chain alkyl or alkenyl group, and R2 is a C1-C4 straight-chain alkyl or alkenyl group.
8. The scandium or yttrium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, R1 and R3 are all the same and are C1-C5 linear, branched or cyclic alkyl or alkenyl groups.
9. The scandium or yttrium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, all of R1 to R3 are the same and are C1-C4 linear, branched or cyclic alkyl or alkenyl groups.
10. The scandium or yttrium-containing thin film forming precursor according to claim 1, characterized in that: The scandium or yttrium-containing thin film forming precursor has a viscosity of 60 cP or less.
11. The scandium or yttrium-containing thin film forming precursor according to claim 1, characterized in that: The scanning- or yttrium-containing thin film forming precursor has a melting point of 70° C. or less.
12. The scandium or yttrium-containing thin film forming precursor according to claim 1, characterized in that: The thin film forming precursor additionally contains a solvent.
13. The scandium or yttrium-containing thin film forming precursor according to claim 12, characterized in that: The solvent is C1-C 16 One or more of saturated or unsaturated hydrocarbons, ketones, ethers, glycol dimethyl ether, esters, tetrahydrofuran and tertiary amines.
14. The method for forming a scandium or yttrium-containing thin film according to claim 12, wherein: The solvent is contained in an amount of 1 to 99% by weight relative to the total weight of the thin film forming precursor.
15. The scandium or yttrium-containing thin film forming precursor according to claim 1, characterized in that: The scandium or yttrium-containing compound represented by Chemical Formula 1 is at least one selected from the group consisting of the following chemical structures:
16. A method for forming a thin film containing scandium or yttrium, characterized in that: The method comprises the step of forming a thin film on a substrate using the thin film forming precursor according to claim 1 or claim 12.
17. The method for forming a scandium or yttrium-containing thin film according to claim 16, wherein: The process of forming a thin film on a substrate comprises: a process of forming a precursor thin film by depositing the thin film forming precursor on the surface of a substrate; and The process of reacting the precursor film with a reactive gas.
18. The method for forming a scandium or yttrium-containing thin film according to claim 17, wherein: The step of forming a precursor thin film includes a step of vaporizing the thin film forming precursor and transferring the vaporized precursor into a chamber.
19. The method for forming a scandium or yttrium-containing thin film according to claim 17, wherein: The deposition is performed by one of a dielectric spin coating (spin-on dielectric, SOD) project, a low temperature plasma (Low Temperatur e Plasma, LTP) project, a chemical vapor deposition (Chemical Vapor Deposition, CVD), a plasma chemical vapor deposition (Plasma Enhanced Chemical Vapor Deposition, PECVD), a high density plasma chemical vapor deposition (High Density Plasma-Chemical Vapor Deposition, HDPCVD) project, an atomic layer deposition (Atomi c Layer Deposition, ALD) project or a plasma atomic layer deposition (Plasma-Enhanced Atomi c Layer Deposition, PEALD) project.
20. The method for forming a scandium or yttrium-containing thin film according to claim 16, wherein: The process of forming a thin film on a substrate comprises: A step of forming a thin film by supplying the thin film forming precursor to a substrate and applying plasma.
21. A semiconductor component, characterized in that: A scandium or yttrium-containing thin film produced by the thin film forming method according to claim 16 is included.
Citation Information
Patent Citations
Preparation of lanthanide-containing precursors and deposition of lanthanide-containing films
KR101660052B1
Lanthanum precursors for depositing lanthanum, lanthanum oxide, and lanthanum nitride films.
KR1020190008427A
Lanthanide precursors and deposition of lanthanide-containing films using the same
KR1020190094238A
Lanthanum compound and methods of forming thin film and integrated circuit device
KR1020190109142A
Yttrium / lanthanide-containing precursor compounds, precursor compositions including the same for forming films, and method of forming yttrium / lanthanide-containing films using the precursor composition
KR1020210084297A